A Preclinical Model of Computerized Cognitive Training: Touchscreen Cognitive Testing Enhances Cognition and Hippocampal Cellular Plasticity in Wildtype and Alzheimer’s Disease Mice - Shepherd, Amy; Zhang, Tracy; Hoffmann, Lucas B.; Zeleznikow-Johnston, Ariel M.; Churilov, Leonid; Hannan, Anthony J.; Burrows, Emma L. (Frontiers in Behavioral Neuroscience, 2021)
With the growing popularity in touchscreen cognitive testing in rodents, it is imperative to understand the fundamental effects exposure to this paradigm can have on the animals involved. In this study, we set out to assess hippocampal-dependant learning in the APP/PS1 mouse model of Alzheimer’s disease (AD) on two highly translatable touchscreen tasks – the Paired Associate Learning (PAL) task and the Trial Unique Non-Matching to Location (TUNL) task. Both of these tests are based on human tasks from the Cambridge Neuropsychological Test Automated Battery (CANTAB) and are sensitive to deficits in both mild cognitive impairment (MCI) and AD. Mice were assessed for deficits in PAL at 9-12 months of age, then on TUNL at 8-11 and 13-16 months. No cognitive deficits were evident in APP/PS1 mice at any age, contrary to previous reports using maze-based learning and memory tasks. We hypothesized that daily and long-term touchscreen training may have inadvertently acted as a cognitive enhancer. When touchscreen-tested mice were assessed on the Morris water maze, they showed improved task acquisition compared to naïve APP/PS1 mice and wild-type (WT) littermate controls. In addition, we show that touchscreen-trained WT and APP/PS1 mice show increased cell proliferation and immature neuron numbers in the dentate gyrus compared to behaviourally naïve WT and APP/PS1 mice. This result indicates that the touchscreen testing paradigm could improve cognitive performance, and/or mask an impairment, in experimental mouse models. This touchscreen-induced cognitive enhancement may involve increased neurogenesis, and possibly other forms of cellular plasticity. This is the first study to show increased numbers of proliferating cells and immature neurons in the hippocampus following touchscreen testing, and that touchscreen training can improve cognitive performance in maze-based spatial navigation tasks. This potential for touchscreen testing to induce cognitive enhancement, or other phenotypic shifts, in preclinical models should be considered in study design. Furthermore, touchscreen-mediated cognitive enhancement could have therapeutic implications for cognitive disorders.